استخدام مياه الصرف الصحي المعالجة في الزراعة المائية لشتول البندورة - زيدان, علي; حيدر, علي (Latakia University Journal -Biological Sciences Series, 2018)
This research work was conducted in Faculty of Agriculture- Tishreen University, using the treated waste water of Aljendereia Water Treatment Station –Lattakia Countryside, for growing tomato seedlings, in order to study the possibility of making adjustment to its ionic balance by adding different levels of some nutrients such as K and N, so that it becomes more balanced from the nutritious point, and so that becomes more suitable to be used as a growth medium in the productive process. The weakness points of the nutritious values of the treated waste water, were defined using the technique of hydroponic agriculture (soilless), Following the Complete Randomized Design (CRD), for two factorial identical experiments to perform this work, by applying (3) levels of both (N) and (K) (0, 100, 200 ppm), singly and in combinations, in the growth medium of the wastewater, with (3) replicates, and neutralizing (P) element by not adding it to all treatments of the first experiment, and adding it with a constant and sufficient concentration (32 ppm P) to all treatments of the second experiment. The growth indicators have been followed through photographs, and measuring the fresh and dry weights of shoots and roots. This work showed better formula for the ionic balance which is most appropriate for growth of tomato seedlings, where the combination of N1K1 which is the addition of 100 mg/L of each of both N and K to the wastewater as a growth medium, proved to be the closest to the proper ionic balance to maintain good growth and health of seedlings and good indicator as a guide base for continuing the experimentation on the field production level and the profitability comparison, as well as getting benefits for environmental protection and health safety through recycling this kind of water in a safe way. نفذ هذا البحث في كلية الزراعة بجامعة تشرين بري شتول نباتات البندورة بمياه الصرف الصحي المعالجة من محطة الجنديرية في ريف اللاذقية بهدف دراسة إمكانية تعظيم الاستفادة من هذه المياه المعالجة بإجراء تعديل في تركيبها الكيميائي من ناحية التوازن الأيوني،بإغنائها بمستويات مختلفة من بعض العناصر الغذائية كالبوتاسيوم والآزوت،جعلها أكثر توازناً من الناحية الغذائية وبالتالي أكثر ملاءمة لاستخدامها كوسط لنمو وانتاج النبات. تم تحديد نقاط الضعف لهذه المياهكمحلول غذائي، باستخدام نظام تقنية الزراعة المائية (بدون تربة)،واتباع التصميم كامل العشوائية (CRD) لتجربتين متطابقتين لتنفيذ هذا العمل باختيار ثلاث مستويات من كل من عنصري الـ N والـ K (ppm 200, 100, 0) بشكل افرادي أو متداخل في وسط النمو وبثلاث مكررات، مع تحييد عنصر الفوسفور بعدم اضافته لمياه الصرف الصحي لكل المعاملات في التجربة الأولى ثم اضافته بتركيز ثابت وكاف بحدود (ppm 32)لكل المعاملات في التجربة الثانية.وتمت متابعة مؤشرات النمو للشتولوالتوثيق الفوتوغرافيوأخذ بعض القياسات الميدانية والمخبرية لتحديد الأوزان الطرية والجافة للمجموعين الخضري والجذري. توصل هذا العمل البحثي إلى بيانات تساعد في اختيار أفضل معادلة سماديه تحقق التوازن الأيوني الأنسب لنمو شتول البندورة. حيث أظهرت المعاملة (N1K1) المتمثلة في إضافة 100مغ\ليتر من كل من العنصرين المذكورين إلى مياه الصرف الصحي كوسط للنمو، أنها الأقرب إلى تحقيق التوازن الأيوني المناسب لنموالشتول وصحتها. وتصلح أن تكون مؤشراًلمتابعة التجريب لاستكمال مراحل النمو ميدانيا على مستوى المقارنة الانتاجية والاقتصادية، وتحقيق فوائد بيئية وصحية من خلال إعادة تدوير هذه المياه والتخلص منها بشكل آمن.